ESTIMATES OF GROWTH, MORTALITY, RECRUITMENT PATTERN AND MSY OF IMPORTANT RESOURCES FROM THE MAHARASHTRA COAST - CHAKRABORTY, SUSHANT K.; DESHMUKH, VINAY D.; KHAN, MOHAMMAD ZAFAR; VIDYASAGAR, KUBER; RAJE, SADASHIV G. (Journal of Indian Fisheries Association, 2016)
Based on the data collected from the year 1987- 1991 the growth,mortality and recruitment pattern of eighteen species of fish, twospecies of cephalopods and four species of penaeid prawns have beenpresented in the present communication. The total mortality coefficient,(Z) varied from lowest of 1.20 for O.cuvieri to a highest of 10.78 forP. stylifera. The natural mortality coefficient, (M) varied from 0.52 forT. thalassinus to 3.44 for S.crassicornis.The average annual yield of eighteen species of fish, four species ofprawns and two species of cephalopods are 65,083, 38,404 and 11,373tons as against the MSYof 83,023, 72,460 and 10,475 tons respectively.The MSY estimated for the total fish stock is 1,77,753t where as thepresent yield is 1,14,859t. This indicates that higher yield can beobtained by increasing the effort.